Putin and the return of history : how the Kremlin rekindled the Cold War - Sixsmith, Martin; Sixsmith, Daniel (Bloomsbury Continuum, 2024)
An original and informative look at Russia's thousand-year past, tracing the forces and the myths that have shaped Putin's politics.